2012
DOI: 10.1002/jmri.23913
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience of 3 tesla apparent diffusion coefficient values in differentiating benign and malignant thyroid nodules

Abstract: This study suggests that the ADC values of nodules measured with a 3T MRI scanner could help in differentiating benign thyroid nodules from malignant nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The ADC values of the phantoms almost covered the ADC values of the normal and tumor tissues of the human body that are measured clinically by 3T MRI, as summarized in Table I (1,3,58,1719). Table I indicates the sucrose concentration of the ADC phantoms at 37°C, which mimic each tissue of the human body using the empirical formula.…”
Section: Discussionmentioning
confidence: 67%
“…The ADC values of the phantoms almost covered the ADC values of the normal and tumor tissues of the human body that are measured clinically by 3T MRI, as summarized in Table I (1,3,58,1719). Table I indicates the sucrose concentration of the ADC phantoms at 37°C, which mimic each tissue of the human body using the empirical formula.…”
Section: Discussionmentioning
confidence: 67%
“…Our results showed that the ADC values of malignant nodules were significantly lower than those of benign ones. A few studies also obtained the same results; however, neither the reported ADC values of thyroid nodules nor the optimal cutoff ADC values for differentiating malignant from benign nodules reached a consensus . We believe that these variable results from the literature may be due to different DWI techniques and to different methods for ROI selection.…”
Section: Discussionmentioning
confidence: 87%
“…Diffusion‐weighted imaging (DWI) is reported to be valuable in differentiating malignant and benign thyroid nodules, and to be used as an adjunct to FNAB . Moreover, recent studies have suggested that apparent diffusion coefficient (ADC) values derived from DWI also have the potential to predict aggressiveness of thyroid carcinoma .…”
mentioning
confidence: 99%
“…These results revealed that the diffusion effect plays a major role in differentiating malignant thyroid nodules, which may be based on differences in the cell density and histopathologic features of benign and malignant thyroid nodules [18,35]. Some ADC and DKI studies with higher b values (1000 s/mm 2 to 2000 s/mm 2 ) have shown the role of diffusion in differentiating benign from malignant thyroid nodules [36,37]. However, Tan et al "s [11].…”
Section: Discussionmentioning
confidence: 92%